2014
DOI: 10.1080/15257770.2014.904519
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mercaptopurine (6MP) Metabolites and 6MP Metabolic Key-Enzymes in Childhood Acute Lymphoblastic Leukemia

Abstract: Pediatric acute lymphoblastic leukemia (ALL) is treated with combination chemotherapy including mercaptopurine (6MP) as an important component. Upon its uptake, 6MP undergoes a complex metabolism involving many enzymes and active products. The prognostic value of all the factors engaged in this pathway still remains unclear. This study attempted to determine which components of 6MP metabolism in leukemic blasts and red blood cells are important for 6MP's sensitivity and toxicity. In addition, changes in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In a pooled analysis of 22 reports [ 40 , 46 , 48 , 56 , 57 , 58 , 65 , 67 , 70 , 72 , 73 , 75 , 84 , 85 , 91 , 92 , 94 , 96 , 98 , 103 , 105 , 107 ], 6-TGN concentrations were significantly higher in patients with leukopenia (mean difference of 127.06 pmol/8 × 10 8 RBC (95% CI 70.88; 183.24; p < 0.01)). We could observe a considerable heterogeneity between studies ( p < 0.01; I 2 = 90%).…”
Section: Resultsmentioning
confidence: 99%
“…In a pooled analysis of 22 reports [ 40 , 46 , 48 , 56 , 57 , 58 , 65 , 67 , 70 , 72 , 73 , 75 , 84 , 85 , 91 , 92 , 94 , 96 , 98 , 103 , 105 , 107 ], 6-TGN concentrations were significantly higher in patients with leukopenia (mean difference of 127.06 pmol/8 × 10 8 RBC (95% CI 70.88; 183.24; p < 0.01)). We could observe a considerable heterogeneity between studies ( p < 0.01; I 2 = 90%).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the timing of the rash resolution corresponded well with the addition of allopurinol and the improvement of the mercaptopurine metabolites. Symptoms occurring sometime after first exposure to 6-MP could be explained by the fact that skewed metabolism can be shown to be idiosyncratic, with manifestations occurring at any time during maintenance therapy 19,20. Other explanations of this could be that the duration of 6-MP exposure was longer during maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been reported on the influence of the activity of the IMPDH on the metabolism of thiopurine drugs, and none have been conducted on the activity of IMPDH in the erythrocytes in the context of autoimmune diseases. Although considered as the limiting enzyme in the formation of 6‐TGN, we did not find any association between RBC IMPDH activity and 6‐TGN, regardless of the population studied.…”
Section: Discussionmentioning
confidence: 99%